DETERMINAN PERILAKU KESEHATAN IBU PADA MASA KEHAMILAN: KASUS KOTA MEDAN - Yuly Astuti; NFN Widayatun (Research Centre for Population, Indonesian Institute of Sciences, 2018)
Maternal and child mortality is still considered a health issue in Indonesia. Health behavior during pregnancy is an essential factor that determines the health of mother and baby. This study aims to examine the behavior of maternal health during pregnancy in Medan City and to analyze its important social determinants. Quantitative data collection using a survey of 400 households in 20 urban villages in Medan City, North Sumatera Province. This study found that 49% of respondents had good behaviors during pregnancy, while those with moderate and poor behaviors during pregnancy were 22% and 29%, respectively. Ordinal logistic regression model indicates husband education, insurance ownership, service quality, and household financial autonomy as social determinants of maternal health behavior during pregnancy. Many factors influenced maternal health behavior during pregnancy both from supply and demand side of health services. Thus, to improve maternal health behavior during pregnancy, it is essential to develop the mother’s knowledge of the importance of antenatal care. Besides that, health service providers also need to ensure the quality of their health services